On Some Complex Constructions in English - Mkhitaryan, Yelena; Sargissyan, Sophia (Armenian Folia Anglistika, 2007)
The article highlights several syntactic constructions which seem identical on surface level. However, the analysis of deep structures reveals certain syntactic and semantic differences. The article suggests the grammatical notion of a new passive-causative structure.